2021
DOI: 10.3390/cancers13164002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pterostilbene, a Natural Derivative of Resveratrol, in the Treatment of Colorectal Cancer through Top1/Tdp1-Mediated DNA Repair Pathway

Abstract: Topoisomerase 1 (Top1) inhibitor is an effective anticancer drug, but several factors limit its clinical application such as drug inactivation, tyrosyl-DNA phosphodiesterase 1 (Tdp1)-mediated tumor drug resistance, and its toxicity. Our previous study identified pterostilbene (PTE) and resveratrol (RE) to suppress these two proteins by binding to their active center. PTE and RE could inhibit the proliferation of various colorectal cancer cells, induce cell apoptosis, and make cell cycle stay in G2/M phase in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…Other research has also confirmed the reduction of colon cancer cell growth exerted by pterostilbene. The time-and dose-dependent growth inhibitory effect of pterostilbene against six different colon cancer cell lines (CL187, COLO205, HCT-8, SW480, LoVo, and HCT-116) was observed in studies performed by Zhang et al [28], and after 48 h treatment with pterostilbene, the IC50 values ranged from 13.82 and 35.73 µM. Furthermore, the results of our study revealed not only inhibition of growth but also a significant time-and dose-dependent reduction in the proliferation rate of HT-29 after incubation with pterostilbene.…”
Section: Discussionmentioning
confidence: 84%
“…Other research has also confirmed the reduction of colon cancer cell growth exerted by pterostilbene. The time-and dose-dependent growth inhibitory effect of pterostilbene against six different colon cancer cell lines (CL187, COLO205, HCT-8, SW480, LoVo, and HCT-116) was observed in studies performed by Zhang et al [28], and after 48 h treatment with pterostilbene, the IC50 values ranged from 13.82 and 35.73 µM. Furthermore, the results of our study revealed not only inhibition of growth but also a significant time-and dose-dependent reduction in the proliferation rate of HT-29 after incubation with pterostilbene.…”
Section: Discussionmentioning
confidence: 84%
“…7 More recently, it is reported that PTE exhibited potent antitumor activities against various types of cancers. 8,9 PTE was shown to inhibit tumor cell growth by inducing autophagy and apoptosis, 10 altering cell cycle, 11 and inhibiting tumor cell migration and invasion. 12 In addition, PTE was recognized as a safe and tolerable compound in both animals and humans.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar to resveratrol, PTE showed diverse bioactivities, including anti-inflammatory, antiaging, anti-obesity, anti-steatosis, antidiabetic, and neuroprotective effects . More recently, it is reported that PTE exhibited potent antitumor activities against various types of cancers. , PTE was shown to inhibit tumor cell growth by inducing autophagy and apoptosis, altering cell cycle, and inhibiting tumor cell migration and invasion . In addition, PTE was recognized as a safe and tolerable compound in both animals and humans. , Thus, it is believed that PTE is a health-promoting nutraceutical with guaranteed efficacy and safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous small molecule TDP1 inhibitors have been reported ( Dyrkheeva et al, 2021 ; Salomatina et al, 2021 ; Zhang et al, 2021 ), the structural basis of their interactions with the enzyme are poorly understood due to a lack of X-ray crystal structures of TDP1 bound to inhibitors. None-the-less, molecular recognition of DNA-containing substrates has been informed by crystal structures of TDP1 with vanadate or tungstate phosphate mimetics bound at the TDP1 catalytic site, as well as with DNA or substrate surrogates ( Figure 1A ) ( Davies et al, 2003 ; 2004 ).…”
Section: Introductionmentioning
confidence: 99%